IMPLEMENTATION OF SMART CONTRACTS IN INDONESIA: AN ANALYSIS OF FINANCIAL REGULATION, TAXATION, AND CONSUMER PROTECTION - Happy Budyana Sari; Emmy Febriani Thalib; Ni Putu Suci Meinarni (NOTARIIL Jurnal Kenotariatan, 2024)
The urgency of this research lies in the growing significance of smart contracts within the blockchain technology landscape, particularly in Indonesia. Smart contracts offer the potential for automation and trustworthy business processes, with demonstrated applications in sectors such as electric power, higher education, e-commerce, and more. However, alongside their success and potential, challenges have emerged regarding financial regulations, taxation, and consumer protection. This study aims to explore the use and challenges of smart contracts in the context of Indonesian law. It seeks to identify the existing regulatory frameworks, assess the legal implications of smart contract usage, and propose solutions to ensure compliance with financial, tax, and consumer protection regulations in Indonesia. By gaining a better understanding of regulatory requirements and potential challenges, this research aspires to contribute to the development of a more efficient, automated, and secure blockchain ecosystem in Indonesia. The research method used is a literature review, encompassing the collection, selection, evaluation, analysis, and synthesis of relevant literature from various academic and practical sources. The expected outcome of this study is a deeper understanding of blockchain usage for data security within the legal context of Indonesia, along with practical guidance and recommendations for policymakers, legal practitioners, and stakeholders in developing effective regulations for data protection in the increasingly complex digital era.he abstract should be written in one paragraph and should be not more than 250 words. Arial, font size 10, single spacing. Follow the following pattern: General statement about the importance of the topic, gap in literature or discrepancies between theories and practices, purpose of study, method, main findings, and result.